2007
DOI: 10.1097/01.ccm.0000275389.31974.22
|View full text |Cite
|
Sign up to set email alerts
|

Optimal management therapy for Pseudomonas aeruginosa ventilator-associated pneumonia: An observational, multicenter study comparing monotherapy with combination antibiotic therapy*

Abstract: Initial use of combination therapy significantly reduces the likelihood of inappropriate therapy, which is associated with higher risk of death. However, administration of only one effective antimicrobial or combination therapy provides similar outcomes, suggesting that switching to monotherapy once the susceptibility is documented is feasible and safe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
138
3
19

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 242 publications
(166 citation statements)
references
References 31 publications
6
138
3
19
Order By: Relevance
“…The possible role of the combination therapy as a risk factor for death was the most surprising finding from the present study. This is at odds with the findings of several authors who have evaluated treatments for P. aeruginosa infection [19,21,22].…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…The possible role of the combination therapy as a risk factor for death was the most surprising finding from the present study. This is at odds with the findings of several authors who have evaluated treatments for P. aeruginosa infection [19,21,22].…”
Section: Discussioncontrasting
confidence: 54%
“…Nevertheless, methodological precautions were taken to ensure the quality of the study. These included the use of very clear definitions for the therapy (empirical, definitive, inappropriate, delayed and combination), definitions for infections according to the NNIS criteria and use of logistic regression [22,29]. Several findings suggest that its results are coherent, such as the inversely proportional relationship between therapeutic adequacy and the likely degree of resistance; the sensitivity pattern for P. aeruginosa, which was very similar to that reported in the MYSTIC study [5] and another study conducted recently in the state of Pernambuco [27]; and, finally, the finding of greater mortality among shock patients and elderly individuals, which is compatible with the literature on severe infections.…”
Section: Discussionmentioning
confidence: 99%
“…Initial use of combination therapy reduces the likelihood of inappropriate therapy, and has been recommended to avoid the emergence of antimicrobial resistance and to enhance the killing produced by antimicrobials acting synergistically, particularly against VAP produced by P. aeruginosa. 2 However, Garnacho-Montero et al 21 demonstrated that monotherapy with only one active antibiotic provided similar outcomes compared with combination therapy with two active antimicrobials, and suggested that switching to monotherapy once the susceptibility is documented was feasible and safe even against P. aeruginosa.…”
Section: Discussionmentioning
confidence: 99%
“…b The combined antibiotic therapy should consider pathogens with antibiotic resistance (such as MRSA, Pseudomonas species, and gram-negative organisms with ESBL activity) increasing the likelihood that at least one drug may be effective against that strain [187,188].…”
Section: Late Onset And/or Risk Factors For Mdr Organismsmentioning
confidence: 99%